Answer:
Step-by-step explanation:
The overall equation for the reaction that produces P4010 from P406 and O2 is:
P4O6(s) + 8O2(g) → P4O10(s)
This equation can be obtained by adding the two given equations and canceling out the common reactants and products:
P4(s) + 3O2(g) → P4O6(s)
P4(s) + 5O2(g) → P4O10(s)
By multiplying the first equation by 4 and the second equation by 2, we can get the same number of phosphorus atoms on both sides:
4P4(s) + 12O2(g) → 4P4O6(s)
2P4(s) + 10O2(g) → 2P4O10(s)
Adding these two equations gives:
6P4(s) + 22O2(g) → 4P4O10(s) + 2P4O6(s)
Since P4O6 is not the desired product, we can eliminate it from the equation by subtracting 2P4O6(s) from both sides:
6P4(s) + 22O2(g) → 4P4O10(s)
This is the same as:
P4O6(s) + 8O2(g) → P4O10(s)
Therefore, the overall equation for the reaction that produces P4010 from P406 and O2 is:
P4O6(s) + 8O2(g) → P4O10(s